Zamboanga Chavacano: A Survey on Written Practices, Reactions and Impact of its (Standardised) Orthography - Himoro, Marcelo Yuji; Pareja-Lora, Antonio (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Zamboanga Chavacano is the most vibrant Philippine Creole Spanish variety. Since the implementation of the Mother Tongue-Based Multilingual Education (MTB-MLE) program in 2012, it has been taught as a subject and used as a medium of instruction in the public schools of Zamboanga City. Despite the approval of an orthography in 2014, it continues to be written using ad hoc spelling systems influenced by Filipino, English and Spanish to varying degrees. By means of a self-administered questionnaire distributed in social media, this study aims to investigate the level of awareness of the speakers to the orthography, their reactions to it, and show that it may be fairly complex for the average speaker. The results of this survey allowed us to preliminarily identify the contexts in which the language is usually written and devise a suitable corpus of written Chavacano for the study of the spelling errors made by the speakers.